Shield or Sword? Moral Distress in Aged Care Employees Related to Regulation and Compliance - Richard Olley (ACHSM, 2022)
This paper reports on one finding of a qualitative study using interpretive phenomenological analysis (IPA) in a mixed-methods study examining the relationship between leadership style and job satisfaction in Australian aged care employees.  The qualitative data suggest that aged care employees are experiencing moral distress relating to the regulatory environment that governs the aged care sector and the compliance processes adopted by regulators and accreditors. One of the reasons for the design and operationalisation of the regulatory environment is to protect vulnerable consumers, the public and the workforce.  However, the findings of this research are that it is this environment that also causes damage to the aged care workforce.  The question is whether compliance requirements and the regulatory scheme are a shield or sword. The causes of the moral distress were different for leaders and raters. This paper reports on this finding.  Moral distress is one of three undesirable outcomes identified in the study and labelled as Workplace Maladies. Moral distress due to regulatory systems and processes experienced by leaders appears to be caused by different factors than the moral distress experienced by raters.  Leaders experienced moral distress because of the system and methods of regulatory and standards compliance. In contrast, their followership experienced other regulatory processes such as the scope of practice for health professionals and the requirement to supervise and accept responsibility for unregulated workers who do not have a scope of practice.  Unregulated workers reported that the absence of scope of practice is a cause of moral distress. Recommendations are made for changes to the system and processes of compliance assessment and action and for developing a scope of practice for unregulated workers to reduce the moral distress experienced by aged care employees and thus reduce workforce turnover in an already scarce workforce.